Novel SRY-box transcription factor 9 variant in campomelic dysplasia and the location of missense and nonsense variants along the protein domains: A case report - Calvache, Carlos A.; Vásquez, Estefanía C.; Romero, Vanessa I.; Hosomichi, Kazuyoshi; Pozo, Juan C. (Frontiers in Pediatrics, 2022)
Background: Campomelic dysplasia is a rare disorder that involves the skeletal and genital systems. This condition is associated with a diverse set of mutations in the SRY-Box Transcription Factor 9(SOX9) gene. Case presentation: This report presents a case of a 4-year-old female patient with campomelic dysplasia, female sex reversal, type 1 Arnold–Chiari malformation, and bilateral conductive hearing loss and investigated the causal mutation. Whole exome sequencing analysis detected a novel W115X variant in the SOX9 gene. We performed a literature review of the reported cases, demonstrated that the missense variants were located only in the self-dimerization domain (DIM) and high-mobility group box domains, reported that variants in DIM domain do not have sex reversal and identified that the amino acid sequences mutated in the human CD patients are evolutionarily conserved among primates. Conclusions: We suggest that missense variants cannot located in the K2, PQA, and PQS since these domains have a critical function for transcriptional activation or repression of target genes and evolves under purifying selection.